ChemInform Abstract: Synthesis of Homophthalates by [3 + 3] Cyclocondensation Reactions of 1, 3‐Bis(silyloxy)‐1, 3‐butadienes with Silylated Methyl 3, 5‐Dioxohexanoate. Issue 45 (14th October 2013) - Hefner, Jennifer; Villinger, Alexander; Langer, Peter
Abstract 3 Homophthalates (V) are prepared by [3 + 3] cyclocondensation reactions of 1, 3‐bis(silyloxy)‐1, 3‐butadienes with silylated methyl 3, 5‐dioxohexanoate.